Should there be an app for that? Inhibiting and contributing factors to the development of a mobile smart city strategy for Brussels - Nils Walravens (Brussels Studies)
Today, more things than people are connected to the Internet, more mobile than fixed broadband subscriptions are active and more than 50% of the world’s population lives in cities. Smartphones and the mobile services and apps that run on them have become the predominant interface between citizens and the so-called “Smart City”. This however, poses difficulties for cities and local governments that are faced with a plethora of new challenges in a changing public service context. This paper provides nine inhibiting and contributing factors that form initial steps in re-thinking what cities in general, and Brussels specifically, should focus on in their efforts to becoming “smarter”, with mobile as a key starting point.